TRAINING ON ENHANCING FINANCIAL AND MARKETING MANAGEMENT SKILLS FOR “AMERTA JAYA” FOOD PROCESSING SMES IN SADING VILLAGE, BADUNG REGENCY - I G. A. Ketut Giantari; Ni Nyoman Kerti Yasa; I Putu Gde Sukaatmadja; I Gusti Ngurah Jaya Agung Widagda K.; I G. A. Dewi Adnyani; Putu Laksmita Dewi Rahmayanti; I Ketut Sujana; Putu Kintan Maharani; I Gusti Ayu Tirtayani (LPPM Institut Pendidikan Nusantara Global, 2025)
The “Amerta Jaya” small and medium-scale food processing industry (IKM) in Sading Village, Badung Regency, has faced increasingly fierce competition over the past three years. This is due to the growing number of players in the industry, which has negatively impacted sales turnover, falling short of the targets. One way to address this issue is through optimal product marketing. Based on preliminary interviews with Mrs. Retno Ika Suryaningsih, the head of the “Amerta Jaya” Food Processing IKM Center—which consists of 31 members in Sading Village—it was confirmed that there has been a decline in sales turnover, and although some marketing strategies have been implemented, they have not been fully effective. The current marketing efforts—ranging from product presentation, pricing, promotion, to distribution—have yet to reach optimal levels, particularly in terms of expanding to supermarkets or mini markets in Badung and Denpasar. This shortcoming stems from limited marketing capabilities. Furthermore, follow-up interviews revealed that, in addition to limited marketing skills, the “Amerta Jaya” food processing IKM also struggles with financial management. These conditions highlight the need for this community service initiative, which aims to equip IKM entrepreneurs in Sading Village with a comprehensive understanding of the importance of financial and marketing management—from designing appealing culinary products to distributing them through various retailers. Therefore, the objective of this community service program is to equip the members of the “Amerta Jaya” food processing IKM in Sading Village, Badung Regency, with essential knowledge on how to comprehensively manage their finances and product marketing, including connecting them to retailers to ensure easier consumer access to their products. The community service activity was conducted on Saturday, August 10, 2024, at the Sading Village Office and was attended by 17 IKM participants, 17 KKN (student community service) participants from Udayana University assigned to Sading Village, along with the service team. The program was successfully carried out with support from the KKN students stationed in Sading Village, Badung Regency.